2020
DOI: 10.1002/nau.24473
|View full text |Cite
|
Sign up to set email alerts
|

The effect of stroke on micturition associated brain activity: A pilot fMRI study

Abstract: Objective: Cerebral stroke is a unique model for studying the role of the brain in lower urinary tract (LUT) control. By its nature, stroke must change the activity of the brain to cause LUT dysfunction. The objective of this study was to describe changes in micturition-related brain activity in patients who develop LUT symptoms (LUTS) after a cerebral stroke. Materials and Methods: Healthy controls (HC, n = 10) and patients who developed storage LUTS after a cerebral stroke (n = 7) were recruited. Functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The site of lesion responsible for the LUTD seemed to be the pontine tegmentum (adjacent to the PMC), which similar to the experimental observations [109]. A recent fMRI study of seven patients with stroke (mostly lacuna in the basal ganglia) and OAB showed higher activation in the PAG (output area) and cerebellum, whereas activation in the PFC (inhibitory area) was minimum [110].…”
Section: Focal Single Brain Diseases (Stroke)supporting
confidence: 80%
“…The site of lesion responsible for the LUTD seemed to be the pontine tegmentum (adjacent to the PMC), which similar to the experimental observations [109]. A recent fMRI study of seven patients with stroke (mostly lacuna in the basal ganglia) and OAB showed higher activation in the PAG (output area) and cerebellum, whereas activation in the PFC (inhibitory area) was minimum [110].…”
Section: Focal Single Brain Diseases (Stroke)supporting
confidence: 80%
“…5 Another study by Nour et al 21 reported that micturition is associated with increased activity within the pons and several other cortical areas. Kreydin et al's 4 research also indicated that stroke subjects exhibited higher activity in the periaqueductal gray and cerebellum during bladder filling and bladder voiding. Our study also revealed that a group of successful-removal urinary catheter compared to groups of failed-removal urinary catheter were found to be significantly different at sites of intracerebral hematoma (P = 0.004).…”
Section: Discussionmentioning
confidence: 94%
“…It has been estimated that up to 94% of patients with stroke have at least one lower urinary tract symptom. Kreydin et al 4 demonstrated that stroke patients exhibit a distinct pattern of brain activity during bladder filling and emptying, compared to healthy controls. They hypothesized that if the disparity could be attributed to impaired neural signaling, then it would prevent recruitment of higher cortical centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations